The Effect of Interpersonal Communication on the Performance of Employees of PT. Elite Karya Mandiri - Devi Larasanti; Fa’uzobihi Fa’uzobihi; Junengsih Junengsih; Pristanto Ria Irawan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Interpersonal communication applied in the company environment is a more dialogical communication by emphasizing self-openness which can often lead to feedback and understanding with each other, this is done in the PT. Elite Karya Mandiri as an effort to improve the performance of its employees. The purpose of this study was to determine interpersonal communication on the performance of PT. Elite Karya Mandiri. This study used quantitative descriptive methods with data collection techniques through the distribution of questionnaires, and library data. In this study using a saturated sampling method used a total of 47 employees of PT. PT. Elite Karya Mandiri, using simple linear regression data analysis techniques. The results of this study show that there is an influence between interpersonal communication on the performance of PT. Elite Karya Mandiri. Strong positive influence and has an influence contribution of 61.3% on employee performance variables. The results of this study are expected to contribute to future research.